1991
DOI: 10.1080/01496399108050475
|View full text |Cite
|
Sign up to set email alerts
|

Soil Clean-Up by Surfactant Washing. I. Laboratory Results and Mathematical Modeling

Abstract: The removal of weathered-in PCBs from clayey soil by surfactant washing is demonstrated at bench scale. Spent surfactant solution was treated for recycle at bench scale by countercurrent liquid-liquid extraction for the removal of nonvolatile contaminants, and by thin film aeration in packed columns for removal of volatile organics. A correlation of micelle/water partition coefficients with octanoll water partition coefficients reported earlier by Valsaraj et al. is extended to several additional compounds. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…In this method, hydrophobic organics are solubilized in the hydrocarbon phase via surfactant micelles (Clarke et al, 1991). Wash-off liquids containing DDT and its metabolites are then dechlorinated in the next step using different methods, such as degradation using zero-valent iron under anaerobic conditions (Ghazali et al, in press;Sayles et al, 1997) …”
Section: Remediation Of Ddt-contaminated Soil Using Optimized Mixturementioning
confidence: 99%
See 3 more Smart Citations
“…In this method, hydrophobic organics are solubilized in the hydrocarbon phase via surfactant micelles (Clarke et al, 1991). Wash-off liquids containing DDT and its metabolites are then dechlorinated in the next step using different methods, such as degradation using zero-valent iron under anaerobic conditions (Ghazali et al, in press;Sayles et al, 1997) …”
Section: Remediation Of Ddt-contaminated Soil Using Optimized Mixturementioning
confidence: 99%
“…The optimum contact time is determined by several factors, including the structure of the soil and the size of a container (column) used for the washing. The results obtained from modeling the batch soil-washing process by Clarke et al (1991) indicated that a contact time of one hour efficiently removes the contaminants when the column radius is 2 cm. However, the removal efficiency is decreased enormously when the radius is increased to 5 cm.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…For example, specific studies have been carried out for washing soils/sediments contaminated with organics 2,4,15 and inorganics 1,8,9,13,16 and also modeling the sorption and desorption phenomenon. 17 Many isolated research efforts on development and application of quantitative structure activity relationships (QSARs) for predicting the sorption and desorption equilibrium at the activated carbon/water interface or activated carbon/air interface [18][19][20][21][22] have been reported in the literature. However, no studies on modeling the soil-washing techniques and incorporating the QSARs for prediction of the thermodynamic limits of sorption and desorption into the soil-washing model have been reported.…”
Section: Discussionmentioning
confidence: 99%